Parametric Optimization of Load Bearing Elements for Composite Wing of an Unmanned Aerial Vehicle - Aung Naing Lin (EDP Sciences, 2021)
This paper describes the optimizing results of structural elements of the composite wing of an unmanned aerial vehicle. The thickness and composite lay-up structure of load-bearing elements and wing skin are determined using the ANSYS software package. The optimal structure is presented using the Pareto set method of the “ideal center” basing on four criteria: minimum mass, deflection, normal stress, and maximum safety factor of the wing. Verification calculations were carried out to determine the safety factor of the load-bearing wing structure using a geometrically nonlinear model in FEMAP software.